Effects of different sterilization processes on the properties of a novel 3D‐printed polycaprolactone stent. (28th May 2018) - Guerra, Antonio J.; Cano, Paula; Rabionet, Marc; Puig, Teresa; Ciurana, Joaquim
Abstract : Bioresorbable stents (BRS) offer the potential to improve long‐term patency rates by providing support just long enough for the artery to heal itself. While manufacturing methods to produce BRS using the appropriate architecture, material and mechanical studies, etc., have received much attention, the effects subsequent sterilization methods have on BRS properties are overlooked. Sterilization process can change a device's properties. This work presents the effects ethanol, ultraviolet light (UV), and antibiotic sterilization processes at 0.5, 1, 2, 4, 8, and 16 hours have on a novel 3D‐printed polycaprolactone stent. The stents were analysed using sterility tests, scanning electron microscopy, differential scanning calorimetry, thermogravimetric analysis, mass spectrometry, for molecular weight, and degradation tests. Results have shown ethanol to be an effective sterilization treatment as it barely affected the material's properties. On the other hand, UV had a considerable influence (mainly produced by the photodegradation of UV irradiation) on crystallinity and molecular weight. Lastly, while antibiotic sterilization did not affect crystallinity to the same degree, it did substantially reduce the molecular weight of the samples. Ethanol results in being the best sterilization method for the high material requirements that medical devices such as stents have.